Pengaruh Sosial Media, Experiential Marketing, dan Kualitas Pelayanan terhadap Kepuasan Konsumen pada Produk Distro Bloodz di Wilayah Jakarta - Bertrand Hendra Cahya; Jatmiko Jatmiko (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of social media, experiential marketing, and service quality on customer satisfaction with Bloodz distro products in the Jakarta area. This research employs a quantitative method, collecting data through questionnaires distributed to Bloodz distro customers. The collected data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the SmartPLS software. The findings reveal that the three variables— social media, experiential marketing, and service quality—positively and significantly affect customer satisfaction. Among these variables, service quality has the most dominant influence. These findings highlight the importance of integrated marketing strategies, enhanced customer experiences, and improved service quality in increasing customer satisfaction.